THE INFLUENCE OF FINANCIAL BEHAVIOR, FINANCIAL LITERACY, AND FINANCIAL MANAGEMENT BEHAVIOR ON THE FINANCIAL WELL-BEING OF MSME ACTORS IN LHOKSEUMAWE, THE ROLE OF FINANCIAL STRESS - Ghazali Syamni; Nur Balkis; Husaini; Darmawati Muchtar; Iswadi; Marbawi (RADJA PUBLIKA, 2025)
This study examines the influence of financial behavior, financial literacy, and financial management behavior on the financial well-being of micro, small, and medium enterprises (MSMEs) in Lhokseumawe, Indonesia, with a particular focus on the mediating role of financial stress. This study is a quantitative study using a purposive sampling technique with a sample of 145 respondents (MSME owners) in Lhokseumawe. The data source comes from primary data obtained through questionnaires. The data analysis technique used is PLS-SEM with SmartPLS software. The results show that financial behavior and financial management behavior have a significant positive influence on financial well-being, while financial stress has a negative impact on financial well-being. Financial stress mediates the relationship between financial behavior and financial well-being, as well as between financial management behavior and financial well-being. These findings underscore the importance of promoting good financial practices and stress management among MSMEs to improve their financial well-being and contribute to local economic development.